Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
Step-by-step explanation:
[tex]\frac{12x}{2x-3x-10}-\frac{x}{x-5}=\frac{12x}{-x-10}-\frac{x}{x-5}\\\\=\frac{12x}{-(x+10)}-\frac{x}{x-5}\\\\=\frac{-12x}{x+10}-\frac{x}{x-5}\\\\=\frac{-12x*(x-5)}{(x+10)*(x-5)}-\frac{x*(x+10)}{(x-5(x+10)}\\\\=\frac{-12x*x-5*(-12x)}{(x+10)(x-5)}-\frac{x*x+x*10}{(x-5)(x+10)}\\\\=\frac{-12x^{2}+60x}{(x+10)(x-5)}-\frac{x^{2}+10x}{(x-5)(x+10)}\\\\=\frac{-12x^{2}+60x-(x^{2}+10x)}{(x+10)(x-5)}\\\\=\frac{-12x^{2} + 60x - x^{2}-10x}{x^{2}+5x-50}\\\\=\frac{-13x^{2}+50x}{x^{2}+5x-50}[/tex]
x = 5
12x = 60
————-
2x - 3x - like terms
2(5) + -3(5)
|
10 + -15 = -5
-5 + 10 (from the espression) = 5
60. 5
——— = 12. ——— = 1
5 5
So 12 - 1 = 11
11 is the answer
12x = 60
————-
2x - 3x - like terms
2(5) + -3(5)
|
10 + -15 = -5
-5 + 10 (from the espression) = 5
60. 5
——— = 12. ——— = 1
5 5
So 12 - 1 = 11
11 is the answer
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.